Class IA PI3Ks regulate subcellular and functional dynamics of IDO1. (7th November 2020) - Iacono, Alberta; Pompa, Andrea; De Marchis, Francesca; Panfili, Eleonora; Greco, Francesco A; Coletti, Alice; Orabona, Ciriana; Volpi, Claudia; Belladonna, Maria L; Mondanelli, Giada; Albini, Elisa; Vacca, Carmine; et al.
Abstract: Knowledge of a protein's spatial dynamics at the subcellular level is key to understanding its function(s), interactions, and associated intracellular events. Indoleamine 2, 3‐dioxygenase 1 (IDO1) is a cytosolic enzyme that controls immune responses via tryptophan metabolism, mainly through its enzymic activity. When phosphorylated, however, IDO1 acts as a signaling molecule in plasmacytoid dendritic cells (pDCs), thus activating genomic effects, ultimately leading to long‐lasting immunosuppression. Whether the two activities—namely, the catalytic and signaling functions—are spatially segregated has been unclear. We found that, under conditions favoring signaling rather than catabolic events, IDO1 shifts from the cytosol to early endosomes. The event requires interaction with class IA phosphoinositide 3‐kinases (PI3Ks), which become activated, resulting in full expression of the immunoregulatory phenotype in vivo in pDCs as resulting from IDO1‐dependent signaling events. Thus, IDO1's spatial dynamics meet the needs for short‐acting as well as durable mechanisms of immune suppression, both under acute and chronic inflammatory conditions. These data expand the theoretical basis for an IDO1‐centered therapy in inflammation and autoimmunity. Abstract : The cytosolic enzyme IDO1 can also act as a signaling molecule in plasmacytoid dendritic cells. Under conditions favoring signaling, IDO1 interacts with PI3K subunits and localizes to early endosomes, a step necessary for immunoregulatory IDO1 signaling in pDCs. Synopsis: The cytosolic enzyme IDO1 can also act as a signaling molecule in plasmacytoid dendritic cells. Under conditions favoring signaling, IDO1 interacts with PI3K subunits and localizes to early endosomes, a step necessary for immunoregulatory IDO1 signaling in pDCs. Under conditions favoring signaling rather than catalytic activity, IDO1 shifts from the cytosol to early endosomes. IDO1 anchoring to early endosomes requires direct interaction with class IA PI3Ks p85 via a previously unknown YxxM motif. Activation of class IA PI3K p110 subunits has a dominant role in the immunoregulatory signaling pathway of IDO1 in pDCs.